A case of impalement injury of finger - May H Ohn; Khin M Ohn (BMJ Publishing Group, 2020)
A 90-year-old man, with Parkinson’s disease, presented to the emergency department with a penetrating finger injury that was caught in the door-handle after a fall. He couldn’t recall the detailed mechanism of fall, but he lost his balance and fell backwards while holding the door-handlewith his right dominant hand.